从林奕含的《房思琪的初恋乐园》谈社会议题与文学实践 = Fang Si-Chi’s First Love Paradise by Lin Yi-Han : the literary intervention in Taiwan’s MeToo movement - 莫静璇 Bok, Jing Xuen (Nanyang Technological University, 2020)
《房思琪的初恋乐园》讲述主人公房思琪常年被住在同一栋大楼的邻居李国华利用教师身份和职权诱奸，最终精神崩溃的故事。《房思琪的初恋乐园》作为一部呈现受暴经验的小说，成功带给中港台#Me Too反性侵运动相当大的启发。由此，本文将首先把房思琪与小说中其他受害少女的个案置于台湾社会的框架中，看到文本如何呈现师生间权势性侵事件的普遍性，而社会结构、权力关系、教育制度等又如何助长此种犯罪，同时导致受害者掉入不被相信甚至被责怪的困境。在社会和法律无法助援的情况底下，文字成为了承接受害者的唯一媒介，林奕含的书写便存在了此种意义。然而，具文学痴情的房思琪却从李国华身上看到了文字、文学的虚伪。对此，本文将专注于房思琪作为个体的创伤经验，看到她在成长过程中从极度向往文学转而质疑文学，却又只能无奈依靠文学找到立足点的矛盾，接着探讨林奕含如何透过房思琪与李国华的对话辩证，对浩浩汤汤的文学传统进行质问和控诉。 Fang Si-Chi’s First Love Paradise narrates a 13-year-old girl, Fang Si-Chi, being entrapped and raped by her neighbor, Li Guo-Hua, using his “power” as a teacher, over Fang, for 5 years. This tragedy ended with a nervous breakdown, of the young Fang, leaving her behind with an irreversible scar. As a novel which describes the experience of being sexually harassed, Fang Si-Chi’s First Love Paradise successfully inspired the #Me Too Movement in China, Taiwan and Hong Kong. Therefore, this thesis initially set up the cases of Fang and other victims into the framework of Taiwan’s society. From there, this thesis discusses the ubiquity of sexual harassment from teachers’ power over students, how the framework of the society, abuse of power and the education system helped grow this act of crime as well as how the victims were trapped in the predicament of disbelief or even being rebuked. Under the helplessness of the society and law, words became the only tool and medium for the author, Lin Yi-Han, to uphold justice. However, the literature-infatuated Fang attracted by the hypocritical words and literature of Li. Regarding that, this thesis focuses on Fang’s trauma as an individual, overlooking her path of growth from yearning for literature to becoming skeptical toward literature, yet she could only rely on literature to establish herself. This thesis then probes into how the Lin interrogated and denounced the tradition of literature through the dialectical dialog of Fang and Li.